Instantaneous VO2 from a wearable device. (February 2018) - Cook, Andrew J.; Ng, Ben; Gargiulo, Gaetano D.; Hindmarsh, Diane; Pitney, Mark; Lehmann, Torsten; Hamilton, Tara Julia
Highlights: A reliable method for calculating instantaneous VO2 is proposed. The developed method is validated against indirect calorimetry by clinical trial. Clinical trial incorporates a range of activities and includes at-risk patient groups. The model is robust showing strong results in sedentary and active periods. Abstract: We present a method for calculating instantaneous oxygen uptake (VO2) through the use of a non-invasive and non-obtrusive (i.e. without a face mask) wearable device, together with its clinical evaluation against a standard technique based upon expired gas calorimetry. This method can be integrated with existing wearable devices, we implemented it in the "Device for Reliable Energy Expenditure Monitoring" (DREEM). The DREEM comprises a single lead electrocardiogram (ECG) device combined with a tri-axial accelerometer and is worn around the waist. Our clinical evaluation tests the developed method against a gold standard for VO2, expired gas calorimetry, using an ethically approved protocol comprising active exercise and sedentary periods. The study was performed on 42 participants from a wide sample population including healthy people, athletes and an at-risk health group including persons affected by obesity. We developed an algorithm combining heart rate (HR) and the integral of absolute acceleration (IAA), with results showing a correlation of r = 0.93 for instantaneous VO2, and r = 0.97 for 3 min mean VO2, this is a considerably improved estimation of VO2 in comparison to methods utilising HR and IAA independently.